Remote Sensing and GIS Techniques for Monitoring Industrial Wastes for Baghdad City - Al-Hashimi, Mohammad Ali; Mohsin, Amjed Naser (Nahrain University College of Engineering Journal, 2008)
The city of Baghdad is located in the central Mesopotamian plain of the Twin Rivers. According to the geological surveys, the whole area is covered by recent sediments of alluvial origin, deposited by successive floods of Tigris and Euphrates rivers, and by wind action. Since Baghdad city is the capital it surrounded by network of industrial areas for different purposes and this, affect the environment. Solid wastes generated from both animal and domestic sources can significantly impair drinking, irrigation, recreational water, other water sources and soil in rural and urban areas therefore it must be monitored and controlled very well to protect the wild life and environment and this represent the goal of research tool used for this purpose is remote sensing and Geographic Information System (GIS) due to their ability of monitoring and analyzing large amount of data. The techniques demonstrated in this research include procedures for developing regional spatial data into a coordinated GIS database, characterizing and identifying wildlife habitat, quantifying and assessing land use change, pollution due to changes in land use and demonstrating the application of these GIS and modeling methods for assessing cumulative environmental effects associated with landuse change. Geographic Information System (GIS) and remote sensing techniques are used to monitor the environment in Baghdad city especially the industrial waste. Using GIS and remote sensing techniques in the environmental assessment give a quick and low cost. Preliminary investigation can be considered as aiding tools to the traditional and detailed investigation procedures.